REVIEW OF THE PREPARATION FOR THE IMPLEMENTATION OF ELECTRONIC SIGNATURES FOR THE AUTHENTICATION OF MEDICAL RECORDS BASED ON A FISHBONE DIAGRAM AT THE NGEBEL COMMUNITY HEALTH CENTER - Afifah Adha Risma Fauziyah; Rumpiati Rumpiati; Ria Fajar Nurhastuti (Institut Kesehatan Pelamonia, 2025)
Afifah Adha Risma Fauziyah, 2025. “A Review of the Implementation of Electronic Signatures for Medical Record Document Authentication Based on the Fishbone Diagram at Puskesmas Ngebel.” Scientific Paper. Supervisor: Rumpiati, S.ST., M.P.H. Diploma III Program in Medical Records and Health Information, Buana Husada College of Health Sciences, Ponorogo.The application of electronic signatures (TTE) is an essential step in supporting digitalization efforts to authenticate medical record documents (RME) in a secure and efficient manner. This study aims to review the readiness for TTE implementation at Puskesmas Ngebel using the Fishbone Diagram analysis (5M: Man, Method, Material, Machine, Money). This research uses a qualitative method with data collection conducted through interviews with respondents including the Head of Puskesmas (for triangulation), medical record officers, registration staff, doctors, and nurses. The results show that Puskesmas Ngebel is still in the initial stage of implementation and faces various obstacles as identified through the Fishbone Diagram analysis. This study is expected to review the level of readiness for TTE implementation and offer solutions to overcome the identified challenges. By applying the Fishbone Diagram approach, this research successfully identifies institutional barriers in preparing for the implementation of electronic signatures for authenticating medical record documents. The findings are expected to contribute to strategic planning for digitalization in community health centers.